2017
DOI: 10.1007/s12079-017-0439-x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Bradykinin receptors worsens the dystrophic phenotype of mdx mice: differential effects for B1 and B2 receptors

Abstract: The Kallikrein Kinin System (KKS) is a vasoactive peptide system with known functions in the maintenance of tissue homeostasis, renal function and blood pressure. The main effector peptide of KKS is Bradykinin (BK). This ligand has two receptors: a constitutive B2 receptor (B2R), which has been suggested to have anti-fibrotic effects in renal and cardiac models of fibrosis; and the inducible B1 receptor (B1R), whose expression is induced by damage and inflammation. Inflammation and fibrosis are hallmarks of Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 66 publications
1
17
0
Order By: Relevance
“…At the level of pathophysiological mechanisms, elevated levels of circulating kallikrein isoform Klk-1 and Klk1-related peptidases suggest altered cellular signaling at the level of the kallikrein-kinin system and the regulation of tissue homeostasis [28] , as well as remodeling of the extracellular matrix and a modification of the immune response in X-linked muscular dystrophy [39] . Thus, comparative saliva proteomics is capable of establishing distinct changes in the biofluid protein complement and this study confirmed that liquid biopsy procedures are suitable bioanalytical tools for the systematic survey of complex pathobiochemical changes in muscular dystrophy [4] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of pathophysiological mechanisms, elevated levels of circulating kallikrein isoform Klk-1 and Klk1-related peptidases suggest altered cellular signaling at the level of the kallikrein-kinin system and the regulation of tissue homeostasis [28] , as well as remodeling of the extracellular matrix and a modification of the immune response in X-linked muscular dystrophy [39] . Thus, comparative saliva proteomics is capable of establishing distinct changes in the biofluid protein complement and this study confirmed that liquid biopsy procedures are suitable bioanalytical tools for the systematic survey of complex pathobiochemical changes in muscular dystrophy [4] .…”
Section: Resultsmentioning
confidence: 99%
“…The kallikrein/kinin and bradykinin signaling axis of vasoactive peptides is involved in blood pressure regulation, tissue homeostasis and renal function. In addition, the endogenous kallikrein/kinin system was shown to be involved in various neurological diseases [27] and appears to play a protective role in dystrophic mdx muscle [28] . Building on these findings and the recent proteomic identification of greatly reduced levels of the kallikrein-1 related peptidase Klk1-b9 in mdx muscle [29] , it was of interest to study the status of kallikreins in mdx-4cv saliva specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the vasoactive peptides can also have local effects on several tissues [ 130 , 131 ]. In skeletal muscle, considerable evidence can be found in the literature showing that the pharmacological modulation of the renin-angiotensin system (RAS) and kallikrein kinin system (KKS) has beneficial effects on skeletal muscle in the context of different pathologies, including muscle atrophy, myopathies, muscular dystrophies, regeneration after trauma and sarcopenia, among others [ 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 ]. This section focuses on the RAS and KKS effects on skeletal muscle physiopathology that occur by the modulation of CCN proteins, with particular emphasis on the regulation of CCN2/CTGF and muscle fibrosis (summarized in Figure 3 ).…”
Section: Regulation Of Ccn2/ctgf and Fibrosis In Skeletal Muscle: Role Of Vasoactive Peptidesmentioning
confidence: 99%
“…In skeletal muscle, both RAS and KKS are involved in modulating muscle mass. Furthermore, in muscle dystrophies, the classic RAS has detrimental effects, and the non-classical RAS axis and KKS seem to be protective [ 147 , 150 , 153 , 154 , 155 ].…”
Section: Regulation Of Ccn2/ctgf and Fibrosis In Skeletal Muscle: Role Of Vasoactive Peptidesmentioning
confidence: 99%
See 1 more Smart Citation